1993
DOI: 10.7326/0003-4819-119-7_part_2-199310011-00024
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Change, All-Cause Mortality, and Cause-specific Mortality in the Multiple Risk Factor Intervention Trial

Abstract: Greater weight variability was associated with a greater risk for cardiovascular disease and all-cause mortality in some types of high-risk men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
3
6

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(163 citation statements)
references
References 0 publications
4
149
3
6
Order By: Relevance
“…In the case of our patients, body weight variations were attributable exclusively to voluntary dieting, as was the case in the Gothenburg Prospective Studies (Lissner et al, 1989). Recently, numerous epidemiological studies have evaluated the in¯u-ence of weight cycling on cardiovascular morbidity and mortality, showing a more signi®cant correlation with weight¯uctuation Ð rather than the body mass index Ð in both cases (Hamm et al, 1989;Lissner et al, 1991;Blair et al, 1993). A signi®cant correlation has also been documented between body-fat distribution indices like the waist-to-hip ratio and the weight¯uctuation index, pointing to the possibility of body-fat redistribution, with an increase in the amount of visceral fat, in subjects with higher degrees of weight cycling (Rodin et al, 1990;Hudgins & Hirsh, 1991).…”
Section: Blood Pressure and Weight Cycling Mt Guagnano Et Almentioning
confidence: 99%
“…In the case of our patients, body weight variations were attributable exclusively to voluntary dieting, as was the case in the Gothenburg Prospective Studies (Lissner et al, 1989). Recently, numerous epidemiological studies have evaluated the in¯u-ence of weight cycling on cardiovascular morbidity and mortality, showing a more signi®cant correlation with weight¯uctuation Ð rather than the body mass index Ð in both cases (Hamm et al, 1989;Lissner et al, 1991;Blair et al, 1993). A signi®cant correlation has also been documented between body-fat distribution indices like the waist-to-hip ratio and the weight¯uctuation index, pointing to the possibility of body-fat redistribution, with an increase in the amount of visceral fat, in subjects with higher degrees of weight cycling (Rodin et al, 1990;Hudgins & Hirsh, 1991).…”
Section: Blood Pressure and Weight Cycling Mt Guagnano Et Almentioning
confidence: 99%
“…2 While gaining a slight amount of weight with increasing age has been associated with a longer life-span, 3 large weight gains elevate the risks for disease and shorten life expectancy. 4 When the body weight rises from normal to increasingly severe obesity, there is a parallel rise in the rate and relative incidence of serious medical conditions 5 and mortality. 6 Obesity in the North American population rose dramatically in the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, after adjusting for available factors, we found no significant association between weight cycling history and lipid measures except TG. It has been suggested that weight cycling might affect cardiovascular risk factors [14][15][16][17][18] ; however, the biological health effects of weight cycling in human studies is controversial 23,44,45) . Two crosssectional studies using weight cycling measures that referred to the individual's assessment of the actual number of times weight had been lost and regained did not support the hypothesis.…”
Section: ) Relation Between Weight Cycling History and Biological Famentioning
confidence: 99%
“…In addition, a number of adverse health effects have been hypothesized to be related to episodes of weight cycling. Several prospective, epidemiological studies relating weight cycling to mortality have been more consistently positive [15][16][17][18] . These studies found that mortality was higher for persons with unstable body weight than for persons whose body weight was relatively stable, and the studies generally concluded that weight cycling resulted from unsuccessful dieting.…”
Section: Introductionmentioning
confidence: 99%